Cryoinjury Mechanisms in the Yeast Fungi Saccharomyces cerevisiae During Freezing in Dimethyl Sulfoxide Aqueous Solution at a Constant Rate in Cylindrical Containers - Sakun, O. V. (Problems of Cryobiology and Cryomedicine, 2010)
The colony-forming ability of the yeast fungi S. cerevisiae suspended in 10% (vol. %) dimethyl sulfoxide – 0.135 M NaCl – water solution after freezing at the rates of 1, 5 and 10°C/min was determined. The method of multi-point thermography demonstrated the dependence of the average cooling rate in a frozen sample on the crystallisation stage of cell suspension on the coolant cooling rate in the cryostat and on the distance from the axles of cylindrical containers with the diameters of 10, 20 and 30 mm. The high colony-forming ability of the microorganisms S. cerevisiae was observed if a considerable amount of cells in a freezing container is cooled at the rates 4–8°C/min on the crystallization stage. The maximal colony-forming ability of the microorganisms S. cerevisiae was achieved if they were frozen in a container with the diameter of 20 mm at the coolant cooling rate of 5°C/min in the cryochamber.